## What is the answer to F(10)= 5(x-1)(2x+3)

Question

What is the answer to F(10)= 5(x-1)(2x+3)

in progress 0
2 weeks 2021-10-09T19:20:50+00:00 1 Answer 0

______________________________________________

→    ”  F(10) = 1035 ” .

______________________________________________

Step-by-step explanation:

______________________________________________

To solve:

For the “right-hand side” of the equation;  substitute “10” for all “x” values:

Given:

F(10) = 5(x – 1)(2x + 3) ;

→   F(10) = 5(10-1)(2*10 + 3) ;

______________________________________________

How, to simplify the right-hand side of the equation;

Solve using PE MD AS ; the mnemonic device for the order of operations to use for simplifying an expression:

Please Excuse My Dear Aunt Sally [or: Susan—either name is fine] :

or the variant:

______________________________________________

Be Excused,  My Dear Aunt Sally/Susan .

______________________________________________

in which the letters of the first words of the sentence in this mnemonic device represent the order of operations performed, as follows:

______________________________________________

(Parentheses, followed by Exponents);  if these occur; in that order;

or:  using the variant:

{Brackets, followed by Exponents};  if these occur, in that order;

— in which “Parentheses” are considered a type of “Brackets” ;

— and in which if both :  Brackets  and  Parentheses occur,

the “Brackets”, take first in the order of operations

[if they occur];   followed by:  “Parentheses” ;

and then followed by:  “Exponents” (if they occur);

_________________________________________

then:  Multiplication (if it occurs) and Division (if it occurs);

However,  instead of Multiplication followed by Division” ;

the difference is that these operations are performed from left to rightas they appear (if both Multiplication and Division occur) within the expression ;

______________________________________________

then:  Addition (if it occurs) and Subtraction (if it occurs);

the difference is that these operations are performed from left to rightas they appear (if both Addition and Subtraction occur) within the expression.

______________________________________________

So:

Given:

F(10) = 5(x – 1)(2x + 3) ;

→   F(10) = 5(10-1)(2*10 + 3) ;

We can calculate—and simplify—the “right-hand side” of the equation; as follows:

We have:

→   “ 5(10-1)(2*10 + 3) ” ;

→   that is;  ” 5 * (10 – 1) * (2*10 + 3) ;

______________________________________________

We do have “parentheses” in this expression:

We shall begin by simplifying the values within the two (2) terms that are enclosed within parentheses:

” (10 – 1) ” ;

10 – 1 = 9 .

______________________________________________

Now, let us continue with the second term that is in parentheses:

” (2*10 +3 ) ” ;

→   2*10 + 3 = ?? ;

→  Note the order of operations rules—{as stated above]; state that “multiplication/division” come before “addition/subtraction” ;

→ So:  ” 2*10 + 3 =  (2*10) + 3 = 20 + 3 = 23 .

On “the right-hand side” of the given equation; we have:

→  ” 5 * (10 – 1) * (2*10 + 3) ;

Replace the terms:  “(10 – 1)” with:  “9” ;

“(2*10 + 3)” with:  “23” ;

And rewrite:

→  F(10) = 5 * 9 * 23 ;

=  45 * 23 ;

=  1035 .

______________________________________________